New Advanced GNSS and 3D Spatial Techniques Applications to Civil and Environmental Engineering, Geophysics, Architecture, Archeology and Cultural Heritage (Lecture Notes in Geoinformation and Cartography,, 2018)
This book provides the latest research on and applications of advanced GNSS (Global Navigation Satellite System) and 3D spatial techniques in the fields of Civil and Environmental Engineering, Geophysics, Architecture, Archaeology and Cultural Heritage. It offers an updated reference guide on the above-mentioned topics for undergraduate and graduate students, PhDs, researchers, professionals and practitioners alike.